The impact of Asean-China Free Trade Area (ACFTA) agreement on Indonesia’s major plantation export commodities - Darmanto, Erlambang Budi; Handoyo, Rossanto Dwi; Wibowo, Wisnu (Business: Theory and Practice, 2021)
This study aims to analyze the impact of ASEAN-China Free Trade Area (ACFTA) on the 4 major exports of plantation commodities (including the commodities of coffee, cocoa, rubber, and palm oil) in Indonesia. The trade impact is measured based on the occurrence of trade creation or trade diversion. The negative coefficient as the result of dummy FTA (Free Trade Area) measurement indicates the presence of trade diversion. Meanwhile, the positive coefficient indicates the presence of trade creation. This study examines the export of major plantation commodities of Indonesia to China and compared with the 10 major export destination countries worldwide. The findings show that trade creation exists within the commodities of coffee, rubber, and palm oil while the trade diversion exists in the commodity of cocoa.